2016
DOI: 10.1111/1365-2435.12770
|View full text |Cite
|
Sign up to set email alerts
|

Competing for seed dispersal: evidence for the role of avian seed hoarders in mediating apparent predation among oaks

Abstract: Summary In communities of large‐seeded tree species, generalist seed hoarders often link the temporally variable dynamics of various species in ways that can result in indirect ecological interactions. A special case of such interactions is ‘apparent predation’ – when variation in seed production of one tree species changes the outcome of the interaction between seed hoarders and another tree species from seed dispersal mutualism to predation. We investigated how two species of avian hoarders responded to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…We found that the paired seeds of Q. variabilis and Q. serrata (Paired 3) and the paired seeds of C. oleifera and C. glauca (Paired 4) showed apparent mutualism, supporting previous findings (Kitzberger et al 2007;Garzon-Lopez et al 2015;Xiao & Zhang 2016;Yang et al 2019). The paired seeds of Q. serrata and C. oleifera (Paired 5) and the paired seeds of C. axillaris and C. fargesii (Paired 6) showed apparent predation, supporting previous studies (Lichti et al 2014;Pesendorfer & Koenig 2017;Bogdziewicz et al 2018b). These indirect interactions between sympatric tree species may change the quality of the dispersal services provided by animals to their plant partners (Bogdziewicz et al 2018b).…”
Section: Animal-mediated Indirect Seed-seed Interactionssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the paired seeds of Q. variabilis and Q. serrata (Paired 3) and the paired seeds of C. oleifera and C. glauca (Paired 4) showed apparent mutualism, supporting previous findings (Kitzberger et al 2007;Garzon-Lopez et al 2015;Xiao & Zhang 2016;Yang et al 2019). The paired seeds of Q. serrata and C. oleifera (Paired 5) and the paired seeds of C. axillaris and C. fargesii (Paired 6) showed apparent predation, supporting previous studies (Lichti et al 2014;Pesendorfer & Koenig 2017;Bogdziewicz et al 2018b). These indirect interactions between sympatric tree species may change the quality of the dispersal services provided by animals to their plant partners (Bogdziewicz et al 2018b).…”
Section: Animal-mediated Indirect Seed-seed Interactionssupporting
confidence: 89%
“…Veech ; Dangremond et al ; Norghauer & Newbery ). A few studies revealed that apparent mutualism (Kitzberger et al ; Xiao & Zhang ) and apparent predation (Lichti et al ; Pesendorfer & Koenig ; Bogdziewicz et al ) occur among tree species through seeds by rodents and birds. Moreover, recent studies showed that seed predation and dispersal of a given tree species can be indirectly affected by other sympatric tree species at the neighbourhood scale (Yi et al ; Garzon‐Lopez et al ; Yi & Wang ).…”
Section: Introductionmentioning
confidence: 99%
“…Our limited data suggest that Q. agrifolia produced more viable dispersed acorns than Q. lobata, especially in 1997-a mast year for both species. This could reflect greater fruit production (Barringer et al 2013) and/or species differences in rates of acorn harvest by larder-hoarding acorn woodpeckers (Melanerpes formicivorus) and scatterhoarding scrub jays (Aphelocoma californica; Pesendorfer and Koenig 2017). Nearly half of the natural Q. agrifolia seedlings surveyed in spring 1998 were found under Q. lobata canopies, presumably due to jay dispersal (Carmen 1988).…”
Section: How Do Vertebrate Consumers Influence Oakmentioning
confidence: 99%
“…Such interactions are ubiquitous in nature (Strauss, 1991;Werner & Peacor, 2003) and play pivotal roles in the organization of plant and animal communities (Holt & Bonsall, 2017;Holt & Lawton, 1994). However, while their influence on seed predation and herbivory is widely acknowledged (Caccia, Chaneton, & Kitzberger, 2006;Emerson, Brown, Whelan, & Schmidt, 2012;Garzon-Lopez et al, 2015;Holt & Bonsall, 2017;Werner & Peacor, 2003), their effects on seed dispersal have been largely ignored (Lichti, Steele, Zhang, & Swihart, 2014;Pesendorfer & Koenig, 2017;Shimada, 2001;Xiao & Zhang, 2016). In theory, indirect interactions could slow an invasion when dispersal of the alien species is reduced in the presence of native species.…”
Section: Introductionmentioning
confidence: 99%